PENGGUNAAN MODEL TAI DENGAN MEDIA MODEL DALAM PENINGKATAN PEMBELAJARAN BILANGAN BULAT SISWA KELAS IV SDN 2 TAMANWINANGUN TAHUN AJARAN 2015/2016 NINIK RUDIYANTI1, NGATMAN2, WAHYUDI3 PGSD FKIP UNIVERSITAS SEBELAS MARET, JALAN KEPODANG 67A PANJER, KEBUME - Rudiyanti, Ninik (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Team Assisted Individualization (TAI) in Improving Learning about Integers for the Fourth Grade Students of SD Negeri 2 Tamanwinangun in the Academic Year of 2015/2016. The objectives of this collaborative Classroom Action Research (CAR) is to improve Mathematics learning about integers. This research was conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research showed that: (1) the use of TAI using model has been implemented appropriately through steps as follows: (a) placement test, (b) teams, (c) teaching group, (d) team study, (e) student creative, (f) team score and recognitation, (g) fact test, (g) whole unit class, (2) The use of TAI using model can improve Mathematics learning about integers for the fourth grade students of SD Negeri 2 Tamanwinangun in the academic year of 2015/2016. It was proved by the increase of learning outcomes in the first cycle 86.48%, in the second cycle 88.80%, and in the third cycle 91.65%. (3) There are some problem sencountered in the learning and it can be solved.  Keywords:Team Assisted Individualization, model, integers Abstrak: Penggunaan Model TAI dengan Media Model dalam Peningkatan Pembelajaran Bilangan Bulat Sisswa Kelas IV SDN 2 Tamanwinangun Tahun Ajaran 2015/2016. Penelitian Tindakan Kelas Kolaboratif ini bertujuan untuk meningkatkan pembelajaran bilangan bulat kelas IV SDN 2 Tamanwinangun. Penelitian ini dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa: (1) penggunaan langkah-langkah pembelajaran model TAI dengan media model sudah dilaksanakan sesuai dengan langkah-langkah: (a) placement test, (b) teams, (c) teaching group, (d) team study, (e) student creative, (f) team score and recognitation, (g) fact test, (g) whole unit class, (2) pengggunaan model TAI dengan media model dapat meningkatkan pembelajaran bilangan  bulat siswa kelas IV SDN 2 Tamanwinangun yang dibuktikan pada siklus I persentase ketuntasan siswa mencapai 86,48%, pada siklus II meningkat menjadi 88,80%, dan siklus III meningkat kembali menjadi 91,65%, (3) menemukan kendala dan solusi dalam penggunaan model TAI dengan media model. Kata kunci: model TAI, media model, bilangan bulat